Field laboratory comparison of STANDARD Q Filariasis Antigen Test (QFAT) with Bioline Filariasis Test Strip (FTS) for the detection of Lymphatic Filariasis in Samoa, 2023. - Jessica L Scott; Helen J Mayfield; Jane E Sinclair; Beatris Mario Martin; Maddison Howlett; Ramona Muttucumaru; Kimberly Y Won; Robert Thomsen; Satupaitea Viali; Rossana Tofaeono-Pifeleti; Patricia M Graves; Colleen L Lau (Public Library of Science (PLoS), 2024)
Background To monitor the progress of lymphatic filariasis (LF) elimination programmes, field surveys to assess filarial antigen (Ag) prevalence require access to reliable, user-friendly rapid diagnostic tests. We aimed to evaluate the performance of the new Q Filariasis Antigen Test (QFAT) with the currently recommended Filariasis Test Strip (FTS) for detecting the Ag of Wuchereria bancrofti, the causative agent of LF, under field laboratory conditions. Methodology/principal findings During an LF survey in Samoa, 344 finger-prick blood samples were tested using FTS and QFAT. Microfilariae (Mf) status was determined from blood slides prepared from any sample that reported Ag-positive by either Ag-test. Each test was re-read at 1 hour and the next day to determine the stability of results over time. Overall Ag-positivity by FTS was 29.0% and 30.2% by QFAT. Concordance between the two tests was 93.6% (kappa = 0.85). Of the 101 Mf slides available, 39.6% were Mf-positive, and all were Ag-positive by both tests. Darker test line intensities from Ag-positive FTS were found to predict Mf-positivity (compared to same/lighter line intensities). QFAT had significantly higher reported test result changes than FTS, mostly reported the next day, but fewer changes were reported between 10 minutes to 1hour. The field laboratory team preferred QFAT over FTS due to the smaller blood volume required, better usability, and easier readability. Conclusion/significance QFAT could be a suitable and user-friendly diagnostic alternative for use in the monitoring and surveillance of LF in field surveys based on its similar performance to FTS under field laboratory conditions.